Non-Formal Public History Education: The Mlaku Magelang Strategy in Fostering Historical Awareness among Generation Z - Pina Dhea Tafana; Bunga Hidayati; Juan Fahirza Putra; Meive Greyne Kudampa; Berlindya Budi Astari (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
One of the informal efforts to foster historical awareness is establishing an action-oriented platform that presents historical data tangibly and physically accessibly. This study aims to analyze the strategies of Mlaku Magelang in constructing local historical narratives relevant to the characteristics of Generation Z integrated through the modern elements of walking tours and to uncover the internalizations of local historical values. This study employed a qualitative approach with a descriptive case study design, with data gathered through observation and interviews. David Kolb’s Experiential Learning theory was utilized as the analytical framework. The findings indicate that Mlaku Magelang successfully implemented an adaptive and contextual communication approach tailored to Generation Z's lifestyle by selecting engaging routes and providing tokens of appreciation to participants. Furthermore, the activity leveraged modern elements, including visual aids, historical documents, visual aesthetics, and thematic dress codes worn by storytellers. Through the direct experience of traversing urban spaces, Generation Z participants responded positively, as evidenced by high levels of interaction and the publication of their activities on Instagram. Theoretically, this research contributes to enhancing public historical literacy; practically, it serves as a conceptual reference for digital history pedagogy that blends urban physical activity with social media activism. Ultimately, this study contributes to bridging the intergenerational historical communication gap, preventing identity crises, and strengthening the nation's collective memory in the future.